Safety of cosmetic products in the light of European legislation: Cosmetic Regulation (EC) No 1223/2009 - Savić Snežana; Paunović Jelica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
After several accidental situations in the cosmetics industry which led to fatal outcomes, the reappeared a need to regulate cosmetics manufacturing. On July 1976 Cosmetic Directive 76/768/EEC came into force with the aim to define the safety criteria to which cosmetic products must conform and to prescribe rules for their labelling and packaging. The Directive has been widened by seven amendments and numerous technical adaptations that led to some confusion. On 30 November 2009 the new document came into force that consolidated all additions and changes: Regulation (EC) No 1223/2009 Of The European Parliament And Of The Council of 30 November 2009 on cosmetic products, known as Cosmetic Regulation The main driver for new legal framework has been simplification of procedures and the streamlining of terminology, achieving an unobstructed traffic of cosmetic products across the EU market. The main aim of The Regulation 1223/2009 is to ensure that a cosmetic product is of high-quality, efficient and safe for human health under normal or reasonably foreseeable conditions of use. The most significant changes introduced by the Cosmetics Regulation 1223/2009 include: strengthened safety requirements for cosmetic products; introduction of the notion of 'responsible person'; centralised notification of all cosmetic products placed on the EU market; introduction of the reporting of serious undesirable effects (SUE); new rules for the use of nanomaterials in cosmetic product. One of the most important duty of the responsible person is preparing a Product Information File (PIF). It is a mandatory document for each cosmetic product that is placed on the market in the Europe Union.